Resistensi terhadap Stereotipe Gender dalam Novel Kita Pergi Hari Ini karya Ziggy Zezsyazeoviennazabrizkie - Fitriani, Dian; Warni, Warni; Fitriah, Siti (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This research aims to describe gender stereotypes and explain resistance to gender stereotypes in the novel